Meta-Analysis: Effect of Using Inquiry Based Learning (IBL) Model on Students’ Competence - Ananda, Prima Nora; Usmeldi, Usmeldi (Jurnal Pendidikan Fisika, 2023)
The development of science and technology has led to a process of change in all aspects of education which includes students’ competencies such as attitudes, knowledge, and skills. However, in reality schools students tend to be disinterested when conventional learning like lecture method is carried out, the level of curiosity or research on students is still low, and students are not accustomed to learning independently or exploring new information about a theory. This study aims to determine the effect of Inquiry Based Learning on the students’ competence. This type of research is meta-analysis conducted by summarizing, reviewing and analyzing data from several previous studies. The research sample consisted of 22 articles taken from journals that already had an ISSN. The data analysis technique used in this study is calculating the effect size of each article. Based on the research results, two conclusions were drawn. First, viewed from educational level, Inquiry Based Learning is more effectively applied at the high school level particularly to enhance students’ attitudes and knowledge competencies with an effect size of 2.47 and 1.45, respectively; when concerning skill competency, IBL is more effective to be used at the tertiary level with an effect size of 2.19. Second, the Inquiry Based Learning is more suitable to be used in physics subjects, especially to develop attitude and knowledge competencies, with an effect size of 2.47 and 1.30, respectively; while skill competency is more effectively implemented to teach biochemistry subjects with an effect size of 2.19.